Pengetahuan Dokter Umum tentang Sindroma Ovarium Polikistik di Puskesmas Surabaya, Indonesia. - Julia Elviethasari; Budi Santoso; Budiono; Sulistiawati (Majalah Kedokteran Indonesia, 2020)
Introduction: Early detection to diagnose PCOS as a promotive and preventive effort is needed in PHC.Method: By using a descriptive research design that was conducted on one of the general practitioners in the Maternal and Child Health Polyclinic (MCH) in 30 PHC was targeted by PCOS from August - October 2019. Result: Thirty general practitioners participated in filling out the questionnaire. Obtained results based on risk factors divided into three categories 33.33% good, 50% sufficient and 16.67% deficient, for causes 6.67% good, 40% sufficient and 53.33% deficient and clinical symptoms 6.67 good%, 40% sufficient and 53.33% deficient. Conclusion: General practitioners at the PHC had a sufficient level of knowledge for risk factors categorized, causes were lacking and symptoms of clinics were lacking. This was an important finding so that it was necessary to increase the specific knowledge of PCOS for the main steps of early detection in PHC.